Once daily versus three times daily mesalazine granules in active ulcerative colitis: a double-blind, double-dummy, randomised, non-inferiority trial. Issue 2 (2nd October 2008) - Kruis, W; Kiudelis, G; Rácz, I; Gorelov, I A; Pokrotnieks, J; Horynski, M; Batovsky, M; Kykal, J; Boehm, S; Greinwald, R; Mueller, R; ,
Abstract : Objectives: To determine the therapeutic equivalence and safety of once daily (OD) versus three times daily (TID) dosing of a total daily dose of 3 g Salofalk (mesalazine) granules in patients with active ulcerative colitis. Design: A randomised, double-blind, double-dummy, parallel group, multicentre, international, phase III non-inferiority study. Setting: 54 centres in 13 countries. Patients: 380 patients with confirmed diagnosis of established or first attack of ulcerative colitis (clinical activity index (CAI)>4 and endoscopic index ⩾4 at baseline) were randomised and treated. Interventions: 8-week treatment with either 3 g OD or 1 g TID mesalazine granules. Main outcome measures: Clinical remission (CAI⩽4) at study end. Results: 380 patients were evaluable for efficacy and safety by intention-to-treat (ITT); 345 for per protocol (PP) analysis. In the ITT population, 79.1% in the OD group (n = 191) and 75.7% in the TID group (n = 189) achieved clinical remission (p<0.0001 for non-inferiority). Significantly more patients with proctosigmoiditis achieved clinical remission in the OD group (86%; n = 97) versus the TID group (73%; n = 100; p = 0.0298). About 70% of patients in both treatment groups achieved endoscopic remission, and 35% in the OD group and 41% in the TID group achieved histological remission. About 80% of all patients preferred OD dosing. Similar numbers of adverse events occurred in 55 patients (28.8%) in the OD group and in 61 patients (32.3%) in the TID group, indicating that the two dosing regimens were equally safe and well tolerated. Conclusions: OD 3 g mesalazine granules are as effective and safe as a TID 1 g schedule. With respect to the best possible adherence of patients to the treatment, OD dosing of mesalazine should be the preferred application mode in active ulcerative colitis. ClinicalTrials.gov Identifier: NCT00449722